ANALISIS PERBEDAAN RELEVANSI NILAI DARI NILAI BUKU EKUITAS DAN LABA PER LEMBAR SAHAM TERHADAP HARGA SAHAM PADA PERIODE SEBELUM DAN SESUDAH PENERAPAN SAK BERBASIS IFRS - simorangkir, panubut (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2016)
This study was conducted to examine whether the implementation of GAAP-IFRS based results of any difference relevance of equity book value and share earnings, using the market price of the stock as the dependent variable, the equity book value and share earnings as an independent variable, and the periods before and after the application of GAAP-based IFRS. The analysis uses panel data regression analysis with random effects models. This research was conducted on 51 manufacturer companies listed on the Stock Exchange the period prior to the application of IFRS-based IFRSs 2008-2010 and after the application of GAAP-IFRS based in 2012-2014. The study found that in the period of after the implementation of GAAPIFRS based the relevance of equity book value increased against the market price of the shares, while the relevance of share earnings experienced a significant decrease in stock market prices